ANALISIS KEPUASAN KERJA BUMN DI INDONESIA : STUDI DAMPAK FAKTOR QUALITY OF WORK LIFE - Delya, Jihan Fajari; Senen, Syamsul Hadi; Masharyono, Masharyono (Journal of Business Management Education (JBME), 2018)
Human resources is able to determine the advance or retreat of an organization and plays an important role in the success of any organization. One of the main problems in human resource management is how to find the best way to achieve employee satisfaction. One way to measure the level of employee satisfaction is to know the feelings of employees towards aspects of the job (Quality of Work Life). The purpose of this study was to determine the influence of quality of work life on job satisfaction of employees of PT A. The method used is a mix method. Data analysis techniques used simple linear regression. The results of the research show that the influence of quality of work life on job satisfaction is included in the strong category with the value of the contribution amounted to 60.84%, meaning that if the quality of work life better then it will improve job satisfaction. Quality of work life is an attempt to achieve self-satisfaction and a work environment that is optimal. If job satisfaction is low will have a negative impact on PT. A such as morale decreases, productivity is low and leads to a social environment that is not healthy as well as declining employee performance.